Methods for Remit Voltage Reversal of Proton Exchange Membrane Fuel Cells - Xiong, Zi’ang; Wen, Bo; Banham, Dustin; Chan, Siew Hwa; Xie, Zhiyong; Liang, Yili; Liao, Shijun (Frontiers in Energy Research, 2022)
In the commercialization of the hydrogen fuel cell for the transportation sector, one of the main factors affecting the lifespan of the fuel cell is voltage reversal, especially when the anode of the fuel cell is subject to fuel starvation momentarily during the operation. In this article, mitigation methods for voltage reversal are summarized in three parts, namely, the catalyst approaches, the MEA design approaches, the stack and system strategies approaches, which include the application of a highly active oxygen evolution reaction (OER) catalyst or durable catalyst support in the anode, employing a protective layer for the catalyst layer or optimizing the formula of the catalyst layer or employing a durable GDL, or optimization of stack design or system operation strategies.